Fiscal Stability and Inclusive Growth in Nigeria - Toriola, Anu K.; Aberu, Felix; Amusa, Salami O.; Adeniwura, Oluwatoba O.; Mustapha, Babajide H. (Indonesian Journal of Contemporary Education, 2022)
In Nigeria fiscal stability has deteriorated resulting in high rate of deficits and domestic debt. This study investigates fiscal stability and inclusive growth in Nigeria using annual data from the Central Bank of Nigeria (CBN) Statistical Bulletin from 1985 to 2015. The result Autoregressive Distributed Lag (ARDL) estimation technique used in the study showed that in the short run debt ratio and inflation have a significant negative effect on inclusive growth in Nigeria. However, in the long-run, debt ratio have a significant negative effect on inclusive growth. Fiscal deficit and inflation have a significant positive effect on inclusive growth. The Granger causality test shows a uni-direction causality relationship between inclusive growth and fiscal stability measures running only from debt ratio and fiscal deficit to inclusive growth. It is evident from the result that fiscal stability in Nigeria is characterised by policy inconsistency and high level of macroeconomic uncertainty indicating high level of fiscal instability. It was suggested that government need to reduce the size of its deficits, broaden the revenue base by increasing the contribution from non-oil sources.